Hubungan antara Tipe Kepribadian Populer dengan Perilaku Asertif - Wiwik Zainar Sri Utami; Lu’luin Najwa (Jurnal Paedagogy, 2020)
The purpose of this study was to determine the relationship between popular personality and assertive behavior of SMAN 2 Pujut Central of Lombok in Academic Year 2019/2020. The population in this study were all students of SMAN 2 Pujut totaling 360 students. The sampling technique uses population research techniques. Data collection techniques in this study used the questionnaire method as the main method while observation, interviews, and documentation as a complementary method. The analysis technique in this study uses the Product Moment Correlation formula. The results of this study obtained r count greater than r table (0.989> 0.233) then the null hypothesis (Ho) is rejected while the alternative hypothesis (Ha) is accepted at the 5% significance level. The conclusion in this study is there is a relationship between popular personality and assertive behavior of SMAN 2 Pujut in Academic Year 2019/2020, then the results of this study are significant.